Blended Learning Approaches for Developing Communicative Competence in English Among Academic Lyceum Learners - Nargiza Yusupova (Indonesian Journal Publisher, 2025)
This article explores the effectiveness of blended learning approaches in enhancing communicative competence among academic lyceum learners in Uzbekistan. Specifically, it focuses on the integration of Google Classroom and Padlet into English language instruction to support speaking and writing skills. Through an action research design, involving 24 second-year lyceum students, the study analyzes both quantitative data (pre- and post-tests) and qualitative inputs such as student reflections, observations, and surveys. The results reveal significant improvements in students’ fluency, accuracy, coherence, and sociolinguistic appropriateness. The findings underscore the pedagogical potential of blended learning to foster learner autonomy, confidence, and collaboration in language learning